1995
DOI: 10.1177/019262339502300608
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Strain as a Determinant Factor in the Differential Responsiveness of Rats to Chemicals

Abstract: The beneficial effects derived from the use of chemicals in agriculture, energy production, transportation, pharmaceuticals, and other products that improve the quality of life are clearly established. However, continued exposure to these chemicals is only advantageous in conditions where the benefit far outweighs toxic manifestations. By law, determination of risk of toxicity necessitates the use of laboratory animals to establish whether chemical exposure is safe for humans. To simulate the human condition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 83 publications
2
35
2
Order By: Relevance
“…Han-Wistar rats exhibited greater sensitivity to nephrotoxic injury due to cisplatin than the Sprague-Dawley rats, as indicated by the occurrence of changes at earlier time points and at lower dosages in the Han-Wistar rats. Strain differences in the severity of toxic response to chemicals, including nephrotoxicants, are known to occur (Kacew, Ruben, and McConnell 1995;Mazze, Cousins, and Kosek 1973;Newton et al 1983aNewton et al , 1983bTarloff, Goldstein, and Hook 1989). However, this would not be a confounding factor in the evaluation of the diagnostic utility of the biomarkers in this study since biomarkers were assessed at the individual animal level relative to time-matched control animals of the same strain.…”
Section: Discussionmentioning
confidence: 95%
“…Han-Wistar rats exhibited greater sensitivity to nephrotoxic injury due to cisplatin than the Sprague-Dawley rats, as indicated by the occurrence of changes at earlier time points and at lower dosages in the Han-Wistar rats. Strain differences in the severity of toxic response to chemicals, including nephrotoxicants, are known to occur (Kacew, Ruben, and McConnell 1995;Mazze, Cousins, and Kosek 1973;Newton et al 1983aNewton et al , 1983bTarloff, Goldstein, and Hook 1989). However, this would not be a confounding factor in the evaluation of the diagnostic utility of the biomarkers in this study since biomarkers were assessed at the individual animal level relative to time-matched control animals of the same strain.…”
Section: Discussionmentioning
confidence: 95%
“…Many neurobiologic differences have been reported that could impact the choice of 1 species over another for neurotoxicity bioassays (11,20,24,53,85). Examples include disparities in neurochemistry, behavior, and xenobiotic responsiveness that exist between rats of different strains, sexes, and ages (52,70,78) and between rats and mice (103). Subtle differences also exist among various primate species (98).…”
Section: Overviewmentioning
confidence: 99%
“…In like manner, the degree of surface partitioning varies markedly among species in direct relation to phylogenetic position. Therefore (25) and monkey (131) (30,122) and rat (77,78) (36,119,144,161,169). Biochemical disparities, such as regional differences in the quantities and circadian cycling of neurotransmitters (110) and hormones (164), have been documented in rodents (24) and primates (169).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for preexistent disease to animals and considered in estimations of alter adverse responses to toxicant exposure human health risk (1)(2)(3)(4). A solid database is widely acknowledged but poorly under-on human susceptibilities related to prestood.…”
Section: Introductionmentioning
confidence: 99%